Using telehealth to provide outpatient follow‐up to children with avoidant/restrictive food intake disorder. Issue 1 (3rd November 2020) - Peterson, Kathryn M.; Ibañez, Vivian F.; Volkert, Valerie M.; Zeleny, Jason R.; Engler, Christopher W.; Piazza, Cathleen C.
Abstract : The COVID‐19 global health crisis compelled behavior analysts to consider alternatives to face‐to‐face services to treat children with feeding disorders. Research suggests telehealth is one method behavior analysts could use to initiate or continue assessment of and treatment for feeding disorders. In the current paper, we conducted pilot studies in which we analyzed chart records of patients with Avoidant/Restrictive Food Intake Disorder; who graduated from an intensive, day‐treatment program; and transitioned to an outpatient follow‐up program. In Experiment 1, we analyzed the data of participants who received follow‐up both in‐clinic and via telehealth. In Experiment 2, we analyzed goal attainment for participants who received outpatient follow‐up either in‐clinic exclusively or via telehealth exclusively. Results of both studies showed that outcomes were equivalent along most dimensions for in‐clinic and telehealth services. We provide recommendations for telehealth feeding services and discuss other considerations relevant to telehealth service delivery.